Achieved throughput of OFDM‐based cognitive radio systems in the presence of inphase quadrature imbalance. Issue 4 (8th August 2016) - Mohajeran, Seyed Ali; Sadough, Seyed Mohammad Sajad
Abstract: Cognitive radio (CR) systems based on orthogonal frequency‐division multiplexing have so far obtained a great deal of attention in wireless communications requiring higher data rates. It is well known that the highest achievable data rate in a wireless communication system is restricted by some factors including the wireless communication channel and the hardware imperfection, which are unavoidable in practice. One of the most important implementation issues that significantly affects the performance of the receiver and the transmitter is the amplitude and phase imbalance in the inphase and quadrature branches, or for brevity inphase and quadrature imbalance (IQI). This imbalance is due to non‐ideal local oscillators at the transmitter or at the receiver of direct conversion systems. In this paper, the ergodic capacity is investigated in a CR system based on orthogonal frequency‐division multiplexing. We also inspect the outage probability, which is restricted by the common IQI challenge in the transmitter of the secondary user (SU) and in the receiver of the SU in a Rayleigh fading channel. First, we obtain an approximate closed‐form expression for the ergodic capacity and the outage probability in a multi‐carrier system. Then we investigate the special cases in which IQI only exists at the receiver or at the transmitter. We show that when IQI only exists at the transmitter of the SU, the approximate closed‐form outage probability of the SU approaches its exact value. Also, when IQI only exists at the receiver or at the transmitter of the SU, the approximate closed form of the ergodic capacity of the secondary link approaches its exact value. Numerical results validate the obtained analytical expression in the CR system. Our results may serve in the evaluation of the trade‐off between the required quality of service (in terms of secondary achieved throughput and the outage probability) and CR system parameters in the presence of IQI. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In this paper, the ergodic capacity is investigated in a cognitive radio system based on orthogonal frequency‐division multiplexing. We also inspect the outage probability, which is restricted by the common IQI challenge in the transmitter of the secondary user and in the receiver of the secondary user in a Rayleigh fading channel. First, we obtain an approximate closed‐form expression for the ergodic capacity and the outage probability in a multi‐carrier system. Then we investigate the special cases in which IQI only exists at the receiver or at the transmitter.